Treatment of Dandruff with Home Remedies-A Literary Review - Nirosh, R.; Tharshika, B.; Sounthararajan, K. (Uva Wellassa University, 2017)
Dandruff is a scalp disease & common complaint among young adults. Dandruff affects often causes itching, hair loss. Modern system of medicine has less effective remedies for dandruff. Most of the time a prophylactic antibacterial or antifungal treatment is initiated which reduces the symptoms, but does not prevent of recurrence. The term 'Home remedy' is a treatment to cure a disease at home or ailment that employs certain spices, some other medicinal plants or plants parts. The objective of this study was to collect the drugs mentioned in the siddha books and journals and to promote the use of home remedies which are used in day to day practice to treat dandruff. Data were collected from authentic home remedy siddha texts, scientific journals and bases such as pub med. There are some of home remedies which used to treat dandruff possesses anti fungal properties. Most of these remedies typically passed from generation to gen- eration by layperson. By the way these home remedies can be a valuable source of information on medicinal plants. Some medicinal plants used as home remedies to treat dandruff such as Artemisia vulgaris leaves, Melothria maderaspatana leaves, Ocimum sanctum leaves and Curcuma longa rhizome and their efficacy have also been proven through scientific researches. It can be concluded that abundant home remedies are available to treat dandruff. Crush leaves mix with some other ingredients or can use it as raw. Apply it over the scalp directly or can boil with Trigonella corniculata and Citrus aurantifolia can apply.
Keywords: Dandruff; Home remedy; Medicinal plants; Anti-fungal